Meningitis due to Gemella haemolysans after radiofrequency trigeminal rhizotomy. Issue 5 (May 1985) - Mitchell, R G; Teddy, P J
Abstract : Meningitis due to Gemella haemolysans developed in a 73 year old woman after thermolysis of the Gasserian ganglion for trigeminal neuralgia. The taxonomy of this organism is discussed, and previous cases of infection are reviewed.